Pathways from ethnic conflict : institutional redesign in divided societies - Coakley, John. ([S.l.] : Routledge, 2010)
The book begins with an agenda-setting introduction which will provide an overview of the central question being addressed, such as the circumstances associated with the move towards a political settlement, the parameters of this settlement and the factors that have assisted in bringing it about. The remaining contributions will focus on a range of cases selected for their diversity and their capacity to highlight the full gamut of political approaches to conflict resolution. The cases vary in: the intensity of the conflict (from Belgium, where it is potential rather than actual, to Sri Lanka, where it has come to a recent violent conclusion); in the geopolitical relationship between the competing groups (from Cyprus, where they are sharply segregated geographically, to Northern Ireland, where they are intermingled); in the extent to which a stable constitutional accommodation has been reached (ranging from the Basque Country, with a large range of unresolved problems, to South Africa, which has achieved a significant level of institutional stability). This book ranges over the world$1 (Bs major geopolitical zones, including Asia, the Middle East, Africa and Europe and will be of interest to practitioners in the field of international security. This book was published as a special issue of Nationalism and Ethnic Politics .s